PERTUMBUHAN EKSPLAN BUAH NAGA (Hylocereus undatus) PADA POSISI TANAM DAN KOMPOSISI MEDIA BERBEDA SECARA IN VITRO - Handayani, Eka; Samudin, Sakka; Basri, Zainuddin (AGROTEKBIS, 2013)
The aims of this experiment were to obtain the most suitable explant planting position and medium composition for the growth of dragon fruit via in vitro culture.  This experiment used Split Plot Design with the main plot was explant planting position, namely vertical and horizontal positions.  The sub plot was media composition, namely 2 ppm BAP + 0.40 ppm NAA; 3 ppm BAP + 0.20 ppm NAA; 2 ppm BAP + 0.40 ppm NAA + 0.88 ppm vitamin C; and 3 ppm BAP + 0.20 ppm NAA + 0.88 ppm vitamin C.  Data were analysed by using Analysis of Variance and differences between treatmens were determined by Honestly Significant Difference.  Results of this experiment indicated that media composition had a highly significant difference on the growth of dragon fruit explants on each planting position tested.  Medium composition supplemented with 3 ppm BAP + 0.20 ppm NAA planted horizontally showed a good growth with average shoot formation 8.67 shoots and shoot length 1.76 cm per explant.  Intensive root formation was observed at vertical planting position with average 7.50 roots per explant.